THE PROBLEM OF MORAL ALIENATION OF YOUTH IN THE CONTEXT OF MODERN SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Spirituality is that unique social mechanism through which the process of inheritance and transmission of values accumulating the spiritual and practical experience of previous generations takes place. This process has a vector orientation and, consequently, the future of spirituality depends directly on how the values of previous generations will be perceived by subsequent ones.